PENGARUH PENGGUNAAN MIND MAPPING DALAM PEMBELAJARAN FIQIH TERHADAP PEMAHAMAN SISWA - Dodi Irawan (PAI RAFAH, 2019)
This study aims to determine the effect of using mind mapping on fiqih learning on students' understanding in East OKU MTs Negeri 1. This research is experimental research. The population of this study was all eighth grade students, totaling 245 students divided into seven classes. Determination of the study sample using cluster sampling technique namely class VIII.C as the experimental class and class VIII.D as the control class with a total of 32 respondents in the experimental class and 32 students in the control class. The design used in this study is the pretest-posttest control group design. The data collection technique in this study used a test instrument multiple choice of 20 questions that had been validated with validation techniques expert and then validated again with the content validation technique item. The data analysis technique used the independent sample t-test gain test scores of the experimental class and the control class. The results of this study are in the independent sample t-test data gain score obtained by the sig 2-tailed 0.00 value means the probability value is less than 0.05 (0.00<0.05), this shows that Ha is accepted, i.e there was a significant difference in students' understanding of the experimental class with the control class. Based on the results of the hypothesis test it can be concluded that the use of mind mapping in fiqih learning influences students' understanding. Next to see the magnitude of the influence, it is tested again using the effect size. Effect size is a measure of the magnitude of the influence of a variable onother variables. test results Effect size(d) obtained a value of 1.03 so it is included in the high category, which is 0,8 £d£ 2,0 (0,8 £ 1,03 £ 2,0). This shows that the use of mind mapping of fiqih learning has a major influence on student understanding.